Spina bifida occulta in children with nocturnal enuresis - Ebrahim A Elkashlan; Mohamed M Shaaban; Anas M AlShreif; Maged Ghanem (Wolters Kluwer Medknow Publications, 2020)
Background Enuresis is defined as the voluntary or involuntary wetting of clothes or bedding with urine for a period of at least three consecutive months in children older than 5 years of age. It is a common disorder in children affecting about 15-20% of 5-year-old children. Enuretic children have a higher incidence of spina bifida occulta (SBO). Presence of SBO can affect the response of enuretic children to the management. Objective The aim of this study was to detect the incidence of SBO in children with nocturnal enuresis and the response to treatment of these enuretic children with SBO compared with enuretics without SBO. Patients and methods From January 2014 to June 2015, we prospectively reviewed 100 patients who visited Al-Hussain University Hospital in Cairo, Egypt, with nocturnal enuresis as the chief complaint to determine the relationship between the SBO and enuresis and also the response to the treatment of children with and without SBO. Results The overall incidence of SBO in enuretic children was 33% and the presence of SBO could affect the treatment results. Conclusion The incidence of SBO is higher in enuretic children and its presence may adversely affect the response to treatment. The cause-and-effect relationship between SBO and nocturnal enuresis (NE) should not be overlooked and should be further elucidated.